Experiments on risk attitude: The case of Chinese students - Shunichiro Sasaki; Shiyu Xie; Fumio Ohtake; Jie Qin; Yoshiro Tsutsui (Osaka University, Institute of Social and Economic Research (ISER), 2006)
This paper examines Chinese students' risk attitude using buying and selling experiments with lotteries. We found that subjects were more risk averse in the buying experiment than in the selling experiment, suggesting the endowment effect. In the selling experiment, subjects were risk loving when there was a low win probability and risk averse with a high win probability, whereas they were risk averse in the buying experiment. Using the prize money won during the experiment as a measure of wealth, we found decreasing absolute risk aversion. Subjects' risk attitude as revealed in the experiments explains their risky asset holding behavior.
Keywords: C91; D81; 330; risk aversion; economic experiment; China; Risikopräferenz; Glücksspiel; Test; China